Elaborasi Prinsip Environmental pada Lembaga Kemasyarakatan di RT 004 RW 001 Banjar Sugihan Surabaya - Rizal Amanullah; Indrawati Yuhertiana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze and identify the extent to which the principles of Environmental, Social, and Governance (ESG) are implemented in community institutions such as the Neighborhood Association (RT) and Community Association (RW). It focuses on examining waste management and land management practices. The research method used is qualitative with a phenomenological approach. Data collection techniques include observation, interviews, and documentation. Data analysis was conducted using triangulation. The study was carried out in RT 004 RW 001 Banjar Sugihan, Surabaya. The results indicate that the community institutions in RT 004 RW 001 Banjar Sugihan, Surabaya have implemented ESG principles, although several areas still require evaluation and improvement in their application within the community.